The Effectiveness of Counseling Leaflet Method Against Changes in Pregnant Women's Knowledge of the Third Trimester of Post-Saline Contraceptives - Asmirati; Mitra Asriani Amin; Nabila; Aldina Lestari; Sri Eka Juniarli; Murida Wiryanti (Jurnal Life Birth, 2022)
Family planning is an example of direct policy in population control. Strategic intervention in safe motherhood efforts is stated as 4 pillars, namely family planning, antenatal care, clean and safe childbirth, and essential obstetric services. This study used a quasi-experimental research design with pre-test and post-test group designs. Using 50 respondents as a selected sample using Purposive Sampling. The results of the statistical signed rank test obtained the average knowledge of respondents before being given an intervention with a leaflet of 9.76 while after being given an intervention of 16.34 with a P value (Asymp. Sig. (2-tailed)) 0.000 where <0.05 so that it can be concluded that there is a meaningful difference before and after the respondent is given the intervention with leaflet. This proves that leaflet media has a great influence on increasing knowledge.